2015
DOI: 10.1016/s2213-8587(15)00126-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of HDL cholesterol efflux capacity with incident coronary heart disease events: a prospective case-control study

Abstract: SummaryBackgroundAlthough HDL cholesterol concentrations are strongly and inversely associated with risk of coronary heart disease, interventions that raise HDL cholesterol do not reduce risk of coronary heart disease. HDL cholesterol efflux capacity—a prototypical measure of HDL function—has been associated with coronary heart disease after adjusting for HDL cholesterol, but its effect on incident coronary heart disease risk is uncertain.MethodsWe measured cholesterol efflux capacity and assessed its relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
382
5
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(416 citation statements)
references
References 19 publications
21
382
5
8
Order By: Relevance
“…Population studies elucidated HDLs as an independent inverse predictor of cardiovascular disease 30, 31. These epidemiologic findings were confirmed in vitro and in animal models, as supported by promotion of cholesterol efflux from cells or tissues,32 inhibition of vascular inflammation33, and improved endothelial cell function 34.…”
Section: Discussionmentioning
confidence: 86%
“…Population studies elucidated HDLs as an independent inverse predictor of cardiovascular disease 30, 31. These epidemiologic findings were confirmed in vitro and in animal models, as supported by promotion of cholesterol efflux from cells or tissues,32 inhibition of vascular inflammation33, and improved endothelial cell function 34.…”
Section: Discussionmentioning
confidence: 86%
“…Background cholesterol efflux (obtained in the absence of apolipoprotein B–depleted plasma) was subtracted from individual cholesterol efflux values. To correct for interassay variability, CEC was measured with the same pool of 40 healthy volunteers’ serum in each assay, and individual percentage CEC values were divided (normalized) by percentage CEC of control serum in each assay, as described previously 3, 5. Control serum CEC values were required to be within the limits defined by the historical mean of CEC for each model, plus or minus 2 SDs, to allow batch qualification.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol efflux from macrophages occurs mainly toward HDL particles through multiple pathways, including passive diffusion, as well as facilitated ABCG1‐ and SR‐BI–dependent transport and active ABCA1‐dependent transport 2. CEC of HDL represents the fraction of radiolabeled cholesterol exiting macrophages typically after 4 hours of incubation, and higher CEC values have been shown to be associated with reductions of both prevalent and incident cardiovascular disease,3, 4, 5 although conflicting reports have been published 6…”
Section: Introductionmentioning
confidence: 99%
“…Rohatgi et al used fluorescently labeled cholesterol method to measure cholesterol efflux capacity in the Dallas Heart Study, a population-based cohort study, and demonstrated that lower levels of cholesterol efflux capacity at baseline was a significant predictor for the incidence of atherosclerotic cardiovascular disease (CVD) during a 9.4-year follow-up period, independently of traditional risk factors including HDL-C, whereas HDL-C was not associated with the incidence of CVD 15) . Saleheen et al used radiolabeled cholesterol method to measure cholesterol efflux capacity in the EPIC-Norfolk study, a population-based prospective case-control study, and demonstrated that cholesterol efflux capacity was significantly inversely associated with incident CAD independent of established cardiovascular risk factors even after adjusting for HDL-C or apolipoprotein A1 16) . These results, therefore indicate the not level of HDL-C but the HDL function would attract much attention as an important therapeutic target for CAD.…”
Section: Subjectsmentioning
confidence: 99%